Structural performance of large-scale dowelled CLT connections under monotonic and cyclic loading. (1st December 2018) - Ottenhaus, Lisa-Mareike; Li, Minghao; Smith, Tobias
Highlights: Monotonic and cyclic tests of 12 large-scale dowelled CLT connections with 3 layouts. Eurocode 5 strength prediction were safe and good ductility was achieved (3.3–7.1) An overstrength factor of 1.68 was safe for cyclic loading. Connection strength and ductility can be improved by using a CLT-LVL hybrid material. Connection strength and ductility can also be improved by using a wider dowel spacing. Abstract: This paper presents an experimental study on 12 large-scale dowelled CLT connections under monotonic and cyclic loading. The connection design was inspired by hold-downs in tall CLT shear wall systems, however, the connections were loaded uniaxially to assess the accuracy of the strength prediction with Eurocode 5 and to evaluate the connection behavior in terms of strength, stiffness, ductility, energy dissipation, and overstrength based on the load–displacement relationship. Two different connection layouts and two different panel layups were considered in the testing. The test results suggested that the tested connections had on average medium to high ductility (4.8–6.3) without the introduction of an excessive amount of overstrength (1.10–1.63) and the connections were able to dissipate a significant amount of energy. It was also found that connection strength can be significantly improved by replacing the outer timber laminations with Laminated Veneer Lumber (LVL) laminations or by using a wider dowel spacing. Furthermore, the LVL laminations also increased the connection's ductility by a factor of 1.3 under cyclic loading and a factor of 1.4 under monotonic loading. Based on test observations, for dowelled connections it is recommended to use bolts or dowels with threaded ends with nuts and washers in the end row of the connection to avoid opening up of the laminations, thus improving the overall connection behavior.